Analysis of teaching practice: dictation in the first classes of Primary School - Farina, Elisa (Formazione & insegnamento, 2015)
Today as never before, the ongoing social and cultural claim pedagogists to move in a direction in which theory and practice are closely related, in order to undertake research that can face the «real problems» involving training agencies. In order to avoid the risk of a disconnection between theory and practice, the research presented here - still in progress - aims to observe, describe and analyze the practice of the dictation in 13 first classes of Primary School. This teaching npractice, still widespread despite its absence from the most recent Ministerial Directions, needs to be deeply investigated: why do teachers dictate? Is dictation still useful in a society where many students come to school already literate or speak languages in which the phoneme-grapheme relationship is not as clear as in the Italian language? Starting from Emilia Ferreiro’s psychogenetic research on the acquisition of written language, this paper aims to understand the reasons that lead teachers to use the dictation, and the implications that this practice has on the process of acquisition of written language